Literasi Keuangan Organisasi Nirlaba Pada Forum Silaturahmi Badan Kemakmuran Masjid - Alistraja Dison Silalahi; Sri Wardany; Cita Ayni Putri Silalahi; Mohd. Idris Dalimunthe; Riska Ananda Putri; Vivi Nadila; Ummi Kalsum Nasution (Pelita Masyarakat, 2023)
Increasing financial literacy is very important related to skills in making financial management accountability reports for non-profit organizations to realize transparency and accountability. Accounting information and financial reports generated will provide convenience in decision making by management, our team and students carry out community service at the Gathering Forum (Fossil) Mosque Prosperity Board (BKM) Medan Tembung District, located at Jalan Bayangkara No. 411 Indra Kasih Village, Medan Tembung, to be precise, is located at the Al Imam Indra Kasih Mosque in Medan. The implementation is carried out by socialization using the lecture method and Focus Group Discussion (FGD). In this method the community service team leader conveys and presents material related to the title of community service delivered while members distribute material and participant attendance is then carried out by discussion and question and answer methods. The implementation of community service provides benefits for mosques and the community, especially scientific provision in compiling financial reports.